Soil as a Topic in Teaching Geography at School: A Pilot Study With Students in the Basic Course of the Teacher Training for Geography - Drieling, Kerstin (Journal of Geography Education, 2005)
In October 2004 a pilot study about "Soil as a topic in teaching Geography at school" was carried out with students in the basic course of the teacher training for Geography at the Universities of Münster and Dortmund. The result of this study was that soil is primarily a topic in geography lessons. Concerning the subtopics one cannot recognize any main emphasis, however, it became clear that the students do not know single terms as soil horizon or desertification or that these topics are neglected at school. Teachers' lectures and dialogues between teachers and pupils are still prevailing teaching methods while activating methods are used only rarely. In freely formulated answers of the students concerning selected terms of soil science it became clear that their knowledge tends to be superficial and that they are influenced by colloquial language and everyday experiences. Finally the results will be discussed on the basis of relevant didactical literature.